Pengendalian Penyakit Layu Fusarium oxysporum f.sp. capsici pada Tanaman Cabai Rawit Capsicum frutescens di Rumah Kaca dengan Trichoderma sp yang Ditambahkan pada Kompos - PUTRA, I MADE TEDI MAHADI; PHABIOLA, TRISNA AGUNG; SUNITI, NI WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
The utilize of Trichoderma sp Compost Formulation to Control wilt disease of Fusarium oxysporum f.sp.capsici in cayenne pepper Fusarium oxysporum f.sp.capsici is a disease that attacks cayenne pepper. This disease can be suppressed by an infectious pathogen called Trichoderma sp. This study was done at laboratory UPT BPTPH Bali Province started from April 2018 to September 2018. This study was done in order to fine the best dose of Trichoderma sp. that used to control Fusarium oxysporum f.sp.capsici on cayenne pepper The experimental design is randomized block design (RBD) with six treatments and each treatment is replicated 4 times. The result of this study show that application of Tricoderma sp. on cayenne pepper could decrease wilt disease of Fusarium oxysporum f.sp. capsici with minimum percentage of wilt symptoms is T5 only 30% in 16 WAT compare with control 67,5%. The best treatment that can decrease symptoms of wilt desease and increasing the yield of cayenne pepper is the T5 (25 gr/plant) but not significantly affect with T3 (12 gr/plant).